Novos anticoagulantes orais e o risco de sangramento gastrointestinal - Scalcon, Camila de Brum (2019)
This is a systematic review conducted in the MEDLINE (Pubmed) database to assess the incidence of gastrointestinal bleeding associated with the use of new oral anticoagulants (NOACS) compared to warfarin. The MeSH terms were used for the studied NOACS, which were: apixaban, dabigatran, edoxaban and rivaroxaban, associated with the database's own randomized clinical trial filter (RCT). As a complementary search strategy, article references were used to select studies relevant to the objective of the review. Inclusion criteria were: texts in english, portuguese or spanish, performed on humans and adults aged 19 years and over, with no limit on the date of publication. The steps were performed by two independent reviewers. The study was developed in line with the PRISMA protocol guidelines (Key Items for Reporting Systematic Reviews and Meta-analyzes). It was identified 613 publications, 597 were excluded and 16 relevant studies were obtained. According to the inclusion criteria, 5 articles were selected for analysis. Of these, 1 was included from the complementary strategy. Total hemorrhagic events were observed in 4,9% (n=2,093) of participants receiving one of the NOACS and 6% (n=1,773) of those using warfarin. Among them, GI hemorrhage corresponded to 48% (n=1,006) among those receiving NOACS and 32,8% (n=583) among those taking vitamin K antagonists. The overall assessment of bleeding events was lower among NOACS users when compared to warfarin users, however, GI bleeding was more frequent among subjects receiving NOACS therapy. Larger doses were the most associated with GI bleeding.